The Effect of Brand Image, Product Diversity, Electronic Word of Mouth on Product Purchasing Decisions Skintific in Medan City - Andani, Salsabila Maisah (Al-Adzkiya Publisher, 2024)
This study aims to determine the effect of Brand Image, Product Diversity, Electronic Word of Mouth on Purchasing Decisions for Skintific products on Skintific product users in Medan City. The problem in this study is whether Brand Image, Product Diversity, Electronic Word of Mouth on Purchasing Decisions for Skintific product users in Medan City. The population of this study is limited to adolescents 16-24 years of Skintific product users in Medan City, who have used Skintific products, the sample of this study was 100 respondents. The data collection technique used a questionnaire using google form. This research data analysis technique uses a quantitative approach, using Outer Model analysis, Inner Model, and Hypothesis Testing. The results showed that the Brand Image variable (X1) had a positive and significant effect on Purchasing Decisions (Y1), the Product Diversity variable (X2) had a positive and significant effect on Purchasing Decisions (Y2), the Electronic Word of Mouth variable (X2) had no effect on Purchasing Decisions for Teenage Users of Skintific Products in Medan City.